The Legal Position of Foso and Boboso Customary Criminal Sanctions within the Framework of the National Criminal Code in the Jurisdiction of the Sultanate of Ternate - Faisal Faisal; Robert Lengkong Weku; Nurlaila Kadarwati Papuluwa; Isyana Kurniasari Koronas; Arief Budiono (Dinasti Research, 2026)
Foso and Boboso have functional customary legal force within the scope of the Ternate customary community as informal law (living law) to maintain the order of the Ternate customary community, North Maluku. This study analyzes: (1) the legal position of the customary criminal sanctions of foso and boboso in the Se Atorang customary tradition in the Ternate Sultanate of North Maluku and (2) the prospects and challenges of transforming customary criminal law as additional punishment in Law Number 1 of 2023 concerning the Criminal Code in the Ternate Sultanate of North Maluku. The research method used in this study is an empirical legal research method with a live case study approach. The results of the study indicate that the origin of Article 66 paragraph (1) letter f provides recognition of customary sanctions against perpetrators of criminal acts. However, there are problems in its application. This is because customary criminal sanctions, known in Ternate customary law as